A CT-image based pig atlas model and its potential applications in the meat industry. (February 2019) - Ho, H.; Yu, H.B.; Gangsei, L.E.; Kongsro, J.
Abstract: In this communication we present a novel pig atlas model which is represented by a parametric linear Lagrange or cubic Hermite mesh. The model is developed from data points digitized from a 3D pig CT image. In total 84 muscles and 121 bones are included in the atlas, representing the tissue structures most relevant to the industry. We discuss its potential applications in virtual meat cuts and statistical shape analysis for pig breeding and genetics companies.